ACTIVE AND SUSTAINABLE MOBILITY IN THE 2030 (Fiep Bulletin - online, 2026)
Active and sustainable commuting, aligned with the Sustainable Development Goals (SDGs) of the United Nations' 2030 Agenda, represents one of the main contemporary strategies for mitigating urban environmental impacts and promoting public health. This article presents an analysis of the state of the art on sustainable mobility and active commuting, based on recent national and international literature. Objective: To understand how active commuting integrated with public policies, service innovation, tactical urbanism, and environmental education can strengthen the achievement of SDGs 3, 11, and 13, promoting more inclusive and resilient cities. Methodology: Analytical literature review of nine documents, including scientific articles, with a time frame from 2020 to 2025. Results: They point to active and sustainable commuting as a vector for reducing greenhouse gas (GHG) emissions. Conclusion: Active and sustainable commuting improves human health, reduces greenhouse gases, and democratizes urban space, but its effectiveness depends on consistent local policies, integrated management, and social participation.
Keywords: Sustainable urban mobility; Active transport; 2030 Agenda; SDG's